Association Between Time Spent for Internet Gaming, Grade Point Average and Internet Gaming Disorder Risk Among Medical Students - Nia Kurnianingsih; Retty Ratnawati; Dearisa Surya Yudhantara; Rizqi Bagus Setyo Prawiro; Maryam Permatasari; Heidyana Rachma; Adilla Surya Ariadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
The negative and positive consequences of internet games were less explored among medical students’ population. The aim of this current study was to investigated the association between time spent for playing internet games and Grade Point Average (GPA) as well as Internet Gaming Disorder (IGD) risk among medical students. A total of 438 students in academic year 2016-2017 completed the self-report questionnaire, that covered socio-demographic information, GPA, time spent for internet gaming/day, and IGD screening. The statistical analysis used c2 test. The average age of the respondents was 20.2 ±1.57 year. The respondents comprised of 37.13% male and 62.87% female students. The percentage of male and female players was 97.5% and 93.8% respectively. Male students were more at risk of IGD (29.56%) compared to their female counterparts (10.04%). Although time spent for internet gaming/day was associated with IGD risk (p<0.001), it was not associated with GPA (p=0.501). There was no significant GPA difference between students who played internet games <3 hours/day and >3 hours/day and those who never play at all. Further study is required to explore the factors related to GPA among medical students.